The Penggunaan Akun Kedua di Media Sosial Instagram - Deska Muhammad Ghifari Hermulya; Rini Rinawati (Bandung Conference Series: Communication Management, 2023)
Abtract. In this Information era internet helps us on every communication we did everyday, Internet also helps us to accssess social media to fulfil our desire in communication. In this digital era, a lot of people express themselves through photos or videos using social media and one of the biggest social media platform that people used to share their photos and videos are Instagram. In other ways instagram is short of places where people can built their images into something that they want, and it makes people used their account instagram very carefully with what they shared. This condition has affect second account phenomena to become the alternative ways of instagram users for shares their contents into the smaller group and express their emotions freely through their content post.This study is purposed to understand about the second account phenomena, starting meaning and motiveof the second account users on Instagram. This study using qualitative research with phenomenology to get to know more about how second account users delivers their messages through instagram features, and the reasons why users used second account on instagram. This study is using interview methods to the second account users and observed the Instagram as the platform. Second account users interpretation usage of the second account as a medium for shares their private life information or it can be calles as self disclosures.this puporsely to become closer with their friends in the second account. Abstrak. Di era Informasi Internet telah menunjang segala kegiatan komunikasi yang kita lalui sehari-hari, Internet juga membantu kita untuk mengakses media sosial yang dapat memenuhi Hasrat berkomunikasi. Penggunaan Media Sosial Instagram menjadi wadah untuk membagikan dan mengekspresikan diri melewati foto, video dan kata-kata kepada para followersnya, selain itu Instagram juga menjadi tempat bagi para penggunanya untuk mengkonstruksikan diri menjadi seperti yang kita inginkan. Fenomena penggunaan second account menjadi alternatif para pengguna Instagram untuk membagikan dan mengekspresikan diri mereka di dalam ruang lingkup yang lebih kecil serta dapat berkomunikasi dengan lebih jujur dalam membagikan postingan. Maka penelitian ini bertujuan untuk mengetahui bagaimana motif dan makna bagi para Penggunaa second account di Instagram. Penelitian ini menggunakan metode Penelitian Kualitatif dengan pendekatan fenomenologi untuk dapat mengetahui lebih dalam mengenai pengguna second account menyampaikan pesan melalui fitur-fitur yang tersedia. Alasan menggunakan second account dengan Teknik peneltian wawancara melalui Informan pengguna second account serta observasi melalui media sosial Instagram. Para pengguna memaknai penggunaan second account sebagai tempat untuk berbagi keluh kesah dalam keseharaian. Selain itu second account juga dijadikan sebagai wadah untuk membagikan informasi tentang diri sendiri atau bisa dianggap sebagai melakukan self disclosure agar bisa menjadi lebih dekat dengan teman-teman di second account.